PRAGMATICS OF THEORETICAL RESEARCH IN THE SPHERE OF FINANCIAL SECURITY OF ENTERPRISES OF NETWORK STRUCTURES: SAFE MEASUREMENT - STETSKO, Mykola; KVASOVSKYI, Oleksandr (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The work substantiates the necessity of forming an effective model of enterprises of network structures, which ensures their financing based on the principles of innovative development. It has been proven that countries with an unbalanced economic structure as a whole also suffer from the inadequacy of economic security management mechanisms. It is argued that in order to ensure the effective development of the market of national enterprises of network structures, it is necessary to determine its global goal and main purpose. Determining its purpose will ensure the unity of the system and internal incentives for development, speed up the integration into the global system of enterprises of network structures and synchronize the internal interests of the market agents of such enterprises with the interests of the economy as a whole. It is substantiated that the market of enterprises of network structures in Ukraine, being a complete socio-economic system, does not have a clear structural organization of its segments in comparison with corporate enterprises. It is proposed that the solution to the problems of the development of enterprises of network structures in Ukraine must be considered in close connection with the issues of their economic security.
Keywords: enterprises of network structures; financial support; economic security; system of economic security; management of economic security; market-oriented model